Sodium deca-tungstate /polyacrylic acid self-assembled flexible wearable photochromic composite fabric for solar UV detector. (1st December 2020) - Bao, Bingwei; Fan, Ji; Wang, Zehong; Wang, Yu; Wang, Wei; Qin, Xintong; Yu, Dan
Abstract: A flexible and lightweight solar ultraviolet (UV) detector compatible with cotton fabric is prepared by simple hydrogen bonding self-assembly of polyacrylic acid (PAA)and sodium deca-tungstate (SDT). Based on photochromism, the solar UV detector with good detection capabilities and the detection effect are obtained. The as-designed solar UV-induced electron transfer process imparts the detector quick response and visual color changes. The detector was tested on the spot in direct solar light and simulated solar light, which proved its outstanding performance as a flexible, wearable and visualized UV detector. Furthermore, the influence of solar doses and on-off cycle stability were studied. Therefore, the detection device fabricated can be used to indicate the intensity of UV lights by sensitive color changes, which provides a feasible idea for the preparation of novel UV detection devices. Graphical abstract: In this study, the cellulose fiber material cotton fabric was used as the substrate, and the layer-by-layer self-assembly of SDS and PAA was carried out on its surface using hydrogen bonds as the driving force, and a composite fabric with excellent sunlight UV detection performance was obtained. The ultraviolet rays in the sunlight induce the transfer of the electrons on the carboxyl group in the PAA and transfer to the hexavalent tungsten in the clustered SDS, causing it to undergo a reduction reaction, thereby having a rapid color change. In the entire system, the hydrogen bond is not only the driving force and the binding force, but also acts as a bridge for electron transfer between the two components. The electrons flow through the hydrogen bond and transfer between the two components, so that the composite fabric has a reversible sunlight and ultraviolet response. ability. In this study, the cost is low, the toxicity is small, the method is simple, and the response effect is quickly visualized. It has great application potential in smart clothing and ultraviolet detectors. Image 1 Highlights: A solar ultraviolet detector was prepared on the basis of hydrogen bonding LbL self-assembly. The solar ultraviolet detector has the advantages of simple process, flexible, low cost, and visible detection effect. The solar ultraviolet detector can quickly respond to different doses of the sunlight in 5 min.